A Comparative Study of Marginal Adaptation between Monolithic and Layered Zirconia Crowns: A Literature Review - Ezatollah Jalalian; Verishe Rastin (Mashhad University of Medical Sciences, 2022)
Introduction: Marginal adaptation highly affects the long-term success of crowns. This study intends to investigate the marginal adaptation of monolithic zirconia and veneered zirconia crowns. Methods: Based on our searches in PubMed and Google Scholar from 2011 to 2020, 22 articles were obtained, and after studying their full-texts. Five articles that were most related to our subject were selected.  Results: In almost all articles, the greatest mean marginal gap value was recorded for monolithic zirconia, whereas layered zirconia crowns demonstrated the lowest mean marginal gap values.  Conclusion:  Based on finding of the current study, monolithic zirconia restorations had a superior marginal adaptation than layered zirconia restorations. However, clinically both restorations have an acceptable marginal fit